Emission Reduction and Profit-Neutral Permit Allocations - Jean-Philippe Nicolaï (ETH Zurich, CER-ETH - Center of Economic Research, 2015)
The present paper addresses two policy objectives that the environmental regulator aims to accomplish: to implement a market for permits and make regulation acceptable for businesses. Profit-neutral permit allocations are defined as the number of permits that the regulator should give for free so that profits after regulation (i.e. profits that the firm realizes in the market for products plus the value of the allowances granted for free) are equal to profits before regulation. The paper demonstrates that a low number of free allowances is sufficient to meet these two goals. Moreover, even when the reduction is high, the regulator can fully offset losses if the concerned sectors are not in a monopoly context. The suggested model is developed by assuming that firms compete "à la Cournot", use polluting technologies and the demand function is iso-elastic. It is then illustrated by the first two phases of the EU Emissions Trading System.
Keywords: F18; H2; L13; L51; Q2; 330; Pollution permits; Cournot oligopoly; EU-ETS